Konrad Lorenz - Schleidt, Wolfgang M; Oeser, Erhard (Wildfowl, 2013)
During the 1940s and 1950s, Konrad Lorenz pioneered the use of cinematic film for studying bird behaviour, focussing on dabbling duck courtship and the activities of goose species. Observations were made at Lorenz’s research station in Germany and also at the Severn Wildfowl Trust (now the Wildfowl & Wetlands Trust) in the UK. This review paper describes how the films contributed to Lorenz’s research. Detailed information on Lorenz’s editing process and treatment of the data is published separately in the Journal of Ornithology. The original film footage is now available at the Austrian Film Museum, Vienna, Austria (http://www.filmmuseum.at/en. Researchers are invited to apply for access to this archive material.